Anteseden Perilaku Ketidakpatuhan Pajak pada Usaha Mikro, Kecil dan Menengah - Aisyah, Esy Nur; Prajawati, Maretha Ika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This study scrutinizes tax non-compliance by integrating new variables from social and economic approaches such as geopolitics, tax service quality, public governance quality, tax system rate, and penalties. Design/Methode/Approach: This research uses an explanatory research approach on 175 MSMEs in the food and beverage sector in Batu City. Moreover, using a census sampling technique. Research Finding: The study's findings indicate that geopolitics, tax service quality, public governance quality, tax system rate, and penalties significantly influence tax non-compliance among MSMEs. Theoretical contribution/Originality: As a contribution to tax knowledge, this research includes new variables in the tax non-compliance model which include social variables and psychological theory. Practitioner/Policy implication: This research can be utilized to enhance the performance of government institutions and departments. The government, as well as tax authorities, can benefit from this research in developing solutions needed to eliminate or minimize the problem of tax non-compliance. Research limitation: This research only focuses on MSMEs in the food and beverage sector in Batu City.